Isaiah 1:4-9 as a post-exilic reflection - Groenewald, Alphonso (Journal for semitics, 2011)
Israel of the exilic/post-exilic period did not run away from its catastrophic history, but instead seized the political catastrophe as an opportunity to examine its past theologically. No era in Israel's history contributed more to theology than the exile. Furthermore, it is clear from the complex way in which the prophetic books have been compiled over a very long period of time that they were the subject of further reflection and adaptation long after the original prophet had died. Nowhere is this more evident than in the case of the book of the prophet Isaiah. The exilic/post-exilic reworking of the Isaianic tradition has been decisive for the character of First Isaiah and for the image of the prophet. This phase of reworking is characterised by the view that the disasters that befell Judah are to be seen as Yahweh's just punishment of the people's disobedience. This article will focus on Isaiah 1:4-9 as an example in order to indicate how the tradition of Isaiah's prophecies was reworked in order to show that they had received their fulfilment at the time when the fortunes of Judah and Jerusalem reached their lowest ebb.